Whale nation - Williams, Heathcote (Harmony Books, 1988)
Photographs and a long narrative poem celebrate the beauty, intelligence, and usefulness of the whale, while deploring its killing to satisfy the human appetite for non-essentials. Includes a lengthy section of commentary on whales and dolphins over the past 170 years.